How immigration can boost the Japanese economy by mitigating the effects of population aging (2020)
The economic impact of immigration depends on the characteristics of the host countries. Immigration has had positive results in countries like the USA, Australia, Canada, and the UK. This paper seeks to demonstrate how Japan would also benefit from immigration. The main barrier to implementing inclusive policies in Japan is the longstanding cultural belief, that immigrants are invaders instead of equal who can enjoy the same rights as native-born Japanese. The aging of Japan’s population is affecting its labor market where there is more demand than supply, meaning that the overall economy is running below its potential. In order to match demand with supply, Japan needs to contemplate the plausible option of letting in more immigrants to fill up vacancies. If Japan fails to do this, it will see a decline in its output capacity, meaning that it will lose competitiveness and productivity with adverse effects on the economy.